Bacterial biostimulants for climate smart agriculture practices: Mode of action, effect on plant growth and roadmap for commercial products - Ravinder Singh; Sehijpreet Kaur; Sukhveer S. Bhullar; Hardeep Singh; Lakesh K. Sharma (Journal of Sustainable Agriculture and Environment, 2024)
Abstract Amidst the global food shortage and the global climate change challenge, there is an urgent need to double food production by 2050. However, the modern crop production methods, including the use of fertilizers and pesticides, have adverse environmental consequences, exacerbating the climate crisis. To address this challenge, a transition to sustainable agriculture is imperative that can harmonize the issue. Biostimulants offer an eco‐friendly solution, especially bacterial biostimulants centred on plant growth‐promoting rhizobacteria (PGPRs). These biostimulants hold the promise of offering environmentally sustainable solutions to enhance crop productivity. The adoption of PGPR‐based biostimulants in agriculture has gained significant momentum in agricultural research. PGPRs enhance plant growth through multifaceted mechanisms. This review delves into the various modes of action employed by PGPRs to improve plant growth, including their impact on nutrient availability (such as nitrogen fixation and mineral solubilization) and stress mitigation. In addition, the practical implication of PGPR strains in field research has been discussed extensively. Besides, the review outlines the roadmap for commercializing PGPR‐based biostimulants and discusses the associated challenges and limitations. A balanced perspective on the practical implementation of PGPRs in modern agriculture is presented. Exploration of future strategies and directions rounds out the review, emphasizing the necessity of a comprehensive approach to address research gaps and unlock the full potential of PGPR‐based biostimulants for sustainable agriculture. In conclusion, this review underscores the applicability of PGPR‐based biostimulants as an innovative solution to address the current food crisis in the context of climate change.